Correlations between the hierarchical spatial heterogeneity and the mechanical properties of metallic glasses. (15th August 2021) - Song, Jinqian; Zhu, Wenqing; Wei, Xiaoding
Highlights: An analysis method based on Fourier transformation is proposed to quantitatively characterize the hierarchy of the inherent spatial heterogeneity of metallic glasses. The degree of the structural heterogeneity at the nanoscale is found to benefit the deformation ductility by delaying the shear band formation for metallic glasses. Abstract: Understanding the spatial heterogeneity originated from the inherent atomic packing mode in glassy solids is one of the central problems in condensed-matter physics and materials science. Here, based on Fourier analysis, we establish an analysis protocol to measure the spatial heterogeneity of metallic glasses quantitatively. Our method reveals an interesting hierarchy of the spatial heterogeneity, ranging from atomic scale to nanoscale, in metallic glasses inherited from the thermal processes. The trends of the spatial heterogeneity change under mechanical loadings provide valuable information about the onset of the shear instability. More importantly, a positive correlation between the initial nanoscale heterogeneity and the material ductility is found that is consistent with the previously reports. The analysis protocol proposed here provides a new way to explore the structure-property relationship for disordered matters. Graphical abstract: Image, graphical abstract